Corporate Governance ohne Vertrauen? Ökonomische Konsequenzen der Agency-Theorie - Michael Nippa; Jens Grigoleit (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
Both, discussion and legislation in the field of corporate governance have been dominated by new institutional economics, especially agency theory. Due to its restrictive assumptions agency theory systematically disregards some important aspects that influence cooperative interaction between shareholder and manager. In addition to the widely accepted crowding out-effect of intrinsic motivation resulting from measures of explicit control, one can assume that extensive monitoring and performance-based incentive systems will induce a similar crowding out effect of trust. Thus, the objective of our paper is to conceptually prove this thesis. We will show that agency-theory implies a suboptimal high degree of explicit control for various social-psychological factors are neglected. Finally, we derive important implications for developing an alternative corporate governanceapproach, which considers trust as a relevant alternative for designing efficient corporate governance systems.
Keywords: D01; G30; L20; 330; Trust; distrust; corporate governance; agency-theory